Hubungan Gagal Ginjal Kronik dengan Tebal Parenkim Ginjal pada Pemeriksaan USG Abdomen Fokus Ginjal - Alfiani, Nur; Suyono, .; Balgis, . (Nexus Kedokteran Klinik, 2013)
Background: Complication that often occurs in chronic renal failure is the reduction of the kidney size. It widely associates with the thinning of the renal cortex due to pathological process. Unlike the cortex, the pathological process which occurred in renal medulla in chronic renal failure has not fully understood yet. Not many studies have examined the association of chronic renal failure with renal parenchyma overall. Therefore, this study aimed to determine the relationship of chronic renal failure with renal parenchyma width on abdomen USG renal focus. Method: This study was an analytical observational research with cross-sectional approach. Sample were taken using fixed-exposure sampling. Sample consisted of 30 subjects were divided into two groups, chronic renal failure and non chronic renal failure. Samples were then measured for renal parenchyma width using abdomen USG renal focus. The data were analyzed with independent-sample t test. In addition, to control confounding factor that could affect renal parenchyma width, age was selected to be controlled using multiple linear regression analysis. All of the data were analyzed using SPSS 17.0 for windows. Result: Patients with chronic renal failure had renal parenchyma width 7.92Â±2.57 mm (p = 0.001), while patients non chronic renal failure had renal parenchyma width 15.64Â±1.85 mm ( p = 0.001). Furthermore, based on the calculation, the multiple linear regression analysis showed the model equation Y = 16.78 â 7.95 X1 â 1.72 X2. The coefficient of determination (R2) of the regression analysis obtained a value of 0.781 means that 78.1% variation in the parenchyma width (Y) can be explained by variations contained in the chronic renal failure (X1) and age â¥54 years old (X2), while 21.9% is explained by other variables not included in the model equations. Conclusion: This study reveals that there is significant correlation between chronic renal failure and renal parenchyma width (p < 0.05), where chronic renal failure patients have renal parenchyma width thinner than the non chronic renal failure patients. Keywords: Chronic Renal Failure, Renal Parenchyma Width, Age, abdomen USGÂ